2002
DOI: 10.1038/sj.leu.2402572
|View full text |Cite
|
Sign up to set email alerts
|

HERG potassium channels are constitutively expressed in primary human acute myeloid leukemias and regulate cell proliferation of normal and leukemic hemopoietic progenitors

Abstract: An important target in the understanding of the pathogenesis of acute myeloid leukemias (AML) relies on deciphering the molecular features of normal and leukemic hemopoietic progenitors. In particular, the analysis of the mechanisms involved in the regulation of cell proliferation is decisive for the establishment of new targeted therapies. To gain further insight into this topic we report herein a novel approach by analyzing the role of HERG K + channels in the regulation of hemopoietic cell proliferation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
170
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(178 citation statements)
references
References 56 publications
5
170
1
2
Order By: Relevance
“…For these reasons, the identification and characterization of ion channels expressed by CD34 + HSCs are essential prerequisites for biotechnological manipulation or physiological understanding of this cell type. However, direct investigations of ion channel function in CD34 + HSCs are rare and primarily focus on cancer cell lines (Korper et al, 2003;Pillozzi et al, 2002;Shirihai et al, 1998). One study using primary CD34 + HSCs demonstrated the inwardly rectifying K + currents but did not systemically examine the other ion channels (Shirihai et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, the identification and characterization of ion channels expressed by CD34 + HSCs are essential prerequisites for biotechnological manipulation or physiological understanding of this cell type. However, direct investigations of ion channel function in CD34 + HSCs are rare and primarily focus on cancer cell lines (Korper et al, 2003;Pillozzi et al, 2002;Shirihai et al, 1998). One study using primary CD34 + HSCs demonstrated the inwardly rectifying K + currents but did not systemically examine the other ion channels (Shirihai et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Concordantly, some K ϩ channels are upregulated during tumorigenesis and are pro-oncogenic. For example, the HERG channel is constitutively activated in a broad range of cancer cell types, and HERG-mediated K ϩ currents stimulate proliferation of several cell types (48,49). Similarly, the TASK3 channel is up-regulated in a variety of cancers and has been demonstrated to stimulate tumor cell proliferation and apoptosis resistance; mutation of the K ϩ filter abrogated both channel function and proliferative effects (50).…”
Section: Fig 5 Sustained Induction Of Mclca5 By Detachment In Immormentioning
confidence: 99%
“…The human ether a gò-gò related (hERG1) channels (KCNH2 or Kv 11.1, according to the most recent nomenclature) are voltagedependent K þ channels that are overexpressed in human endometrial adenocarcinoma (Cherubini et al, 2000), myeloid leukaemia (Pillozzi et al, 2002) and colorectal cancer (Lastraioli et al, 2004). In addition, they are often overexpressed in neoplastic cell lines of different origin.…”
mentioning
confidence: 99%